Analisa Performansi Bahan Bakar Biogas dan Bensin Terhadap Kualitas Pembakaran Pada Engine Genset 4 Tak 1 Silinder Kapasitas 80 cc - Abdullah, Ilmi; Yudanto, Bagus Giri; Nasution, Arjanggi; Andiko, Rendi (CV. IRA PUBLISHING, 2022)
This research studies the analysis of the performance of biogas fuel on exhaust gas emissions produced by the engine generator set and as an operational generator from gasoline-fueled to biogas fuel, modifications to the carburetor are necessary. In a complete combustion reaction there are inhibitory gases such as carbon dioxide, impurity gases such as hydrogen sulfide, and gases required for combustion such as oxygen, and incomplete combustion will produce monoxide gas. This test was carried out using gas chromatography at 0/no load, 300, 600, 900 Watt loading. The analysis carried out in this study includes the calorific value that occurs, the combustion reaction, power, torque, average adequate pressure, specific fuel consumption, and thermal events that occur in the generator. Based on the results of research conducted, it is more efficient to use purified biogas for the lowest CO2 emissions of 9.1089%, for O2 of 16.7165%. Based on the results of research conducted it is more efficient to use purified biogas for the lowest CO2 exhaust emissions of 9.1089%, for O2 of 16.7165% but in terms of combustion quality, the use of gasoline is better than biogas of 30381 kJ/kg due to the element content higher carbon gasoline.